DIAGNOSTIC ACCURACY OF XPERT MYCOBACTERIUM TUBERCULOSIS/RIFAMPICIN IN DETECTING PULMONARY TUBERCULOSIS FROM BRONCHOALVEOLAR LAVAGE FLUID IN SPUTUM-NEGATIVE PATIENTS (The Research of Medical Science Review, 2025)
BACKGROUND: Pulmonary tuberculosis (TB) remains a major public health concern worldwide, especially in high-burden countries like Pakistan. Although sputum smear microscopy and culture are standard diagnostic tools, their limitations in smear-negative cases necessitate alternative approaches. The Xpert MTB/RIF assay offers a rapid molecular method, but its diagnostic accuracy on bronchoalveolar lavage fluid (BALF) remains understudied in sputum-negative patients.OBJECTIVE: To determine the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of the Xpert MTB/RIF assay on BALF in sputum-negative suspected pulmonary TB cases, using culture as the gold standard.METHODS: This cross-sectional study was conducted at Lady Reading Hospital, Peshawar, over six months, enrolling 679 adult patients with smear-negative pulmonary TB suspicion undergoing bronchoscopy. BALF samples were tested using smear microscopy, culture (gold standard), and the Xpert MTB/RIF assay. Sensitivity, specificity, PPV, NPV, and diagnostic accuracy were calculated from a 2×2 contingency table. Results were stratified by gender and age group. Data were analyzed using SPSS v25.RESULTS: The study included 389 males (57.3%) and 290 females (42.7%) with a mean age of 41.3 ± 14.2 years. Out of 171 culture-positive cases, 145 were also positive by Xpert. Among 508 culture-negative cases, 490 tested negatives with Xpert. The Xpert assay demonstrated a sensitivity of 84.8%, specificity of 96.5%, PPV of 88.9%, NPV of 94.9%, and overall diagnostic accuracy of 93.3%. Stratified analysis showed comparable diagnostic metrics across gender and age groups. The ROC curve yielded an AUC of 0.97, indicating excellent diagnostic performance.CONCLUSION: Xpert MTB/RIF on BALF provides high diagnostic accuracy for detecting pulmonary TB in sputum-negative patients, with excellent sensitivity, specificity, and predictive values. These findings support its use as a reliable frontline diagnostic tool in high TB-burden settings like Pakistan.